The locus coeruleus-norepinephrine system as pacemaker of attention: a developmental mechanism of derailed attentional function in autism spectrum disorder - Bast, Nico; Poustka, Luise; Freitag, Christine M. (European journal of neuroscience, 2018)
Children with autism spectrum disorder (ASD) exhibit diminished visual engagement to environmental stimuli. Aberrant attentional function provides an explanation by reduced phasic alerting and orienting to exogenous stimuli. We review aberrant attentional function (alerting, orienting and attentional control) in children with ASD as studied by neurocognitive and neurophysiological tasks as well as magnetic resonance imaging studies. The locus coeruleus-norepinephrine (LC-NE) system is outlined as a pacemaker of attentional function. The LC-NE system regulates adaptive gain in synaptic signal transmission, which moderates phasic alerting (‘promoting’) and the activation of the ventral frontoparietal attention network within orienting (‘permitting’). In children with ASD, atypical LC-NE activity is proposed as underlying mechanism of aberrant attentional function. It may manifest as (i) increased tonic activity with reduced phasic reactivity to exogenous stimuli, (ii) attenuated bottom-up signalling mitigating salience and predictive reward attribution during phasic alerting, and (iii) reduced activation of the ventral frontoparietal attention system attenuating orienting to exogenous stimuli. Increased tonic pupil dilation and aberrant pupil reactivity are discussed as indicators of atypical LC-NE activity. Pupillometry is outlined as feasible method to assess alerting, orienting and attentional control that can be dissected from the pupil dilation time course. In children with ASD, aberrant attentional function through atypical LC-NE activity is proposed as developmental mechanism leading to reduced social attention as well as social interaction and communication impairments.
Gesehen am 28.08.2019
First published: 15 December 2017